Compensation Peer Group Effects: Evidence from NFL Professional Football - Quinn Keefer; Thomas J. Kniesner (Institute of Labor Economics (IZA), 2024)
Our research interest is in the existence and size of possible peer effects in pay or whether a worker may get a higher salary because another worker does rather than being related to a change in the worker's productivity or market forces. Previous research, which has concentrated on executive pay, suffers from the inability to control for labor market forces. We net out market forces by studying a group of particular U.S. pro football players who are subject to a tightly budgeted unionized institutional arrangement affecting certain players pay set in the offseason. Our empirical results for NFL wide-receivers and cornerbacks during 2013-2022 are that there is an elasticity of average contract value with respect to the largest contract already signed in the offseason of about 0.17. Players we study who sign the largest contract during the offseason at the time of signing generate significant pay spillovers to players signing subsequent offseason contracts, suggesting that their compensation is economically and statistically significantly impacted by peer group reference points.
Keywords: J31; J33; Z21; 330; labor market reference point effects; NFL player pay; fixed effects; quantile regression; influence analysis